The limits of law : Paul Ricoeur and a critical phronesis to engage law, ethics and religion - Marble, Susan (Trinity College (Dublin, Ireland). Department of Religions and Theology, 2008)
This study explores the relationship of law and ethics from the insight, evident for many who have been engaged in law as a profession, that the practice of law encounters limits which point to a broader context in which it has to be embedded: the level of ethical values and moral obligations operative between persons, citizens, and communities. The level of ethics equally encounters limits, as is reflected in the traditional duality between the deontological and the teleological approaches to it. My interest is in attempts to reconcile the two, and Paul Ricoeur’s work in this regard is of particular importance since he also offers bridges to both the theory of law and to religion and biblical faith.
Keywords: Religion, Ph.D.; Ph.D. Trinity College Dublin